Solubilization of proteins from human lymph node tissue and two-dimensional gel storage. - de Marqui, Alessandra Bernadete Trovó; Vidotto, Alessandra; Polachini, Giovana Mussi; Bellato, Cláudia de Mattos; Cabral, Hamilton; Leopoldino, Andréia Machado; de Góis Filho, José Francisco; Fukuyama, Erica Erina; Settanni, Flávio Aurélio Parente; Cury, Patrícia Maluf; Bonilla-Rodriguez, Gustavo Orlando [UNESP]; Palma, Mario Sergio [UNESP]; et al. (My University, 2006)
In the present study, we compared six different solubilization buffers and optimized two-dimensional electrophoresis (2-DE) conditions for human lymph node proteins. In addition, we developed a simple protocol for 2-D gel storage. Efficient solubilization was obtained with lysis buffers containing (a) 8 M urea, 4% CHAPS (3-[(3-cholamidopropyl) dimethylammonio]-1-propanesulfonate), 40 mM Tris base, 65 mM DTT (dithiothreitol) and 0.2% carrier ampholytes; (b) 5 M urea, 2 M thiourea, 2% CHAPS, 2% SB 3-10 (N-decyl-N,N-dimethyl-3-ammonio-1-propanesulfonate), 40 mM Tris base, 65 mM DTT and 0.2% carrier ampholytes or (c) 7 M urea, 2 M thiourea, 4% CHAPS, 65 mM DTT and 0.2% carrier ampholytes. The optimal protocol for isoelectric focusing (IEF) was accumulated voltage of 16,500 Vh and 0.6% DTT in the rehydration solution. In the experiments conducted for the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), best results were obtained with a doubled concentration (50 mM Tris, 384 mM glycine, 0.2% SDS) of the SDS electrophoresis buffer in the cathodic reservoir as compared to the concentration in the anodic reservoir (25 mM Tris, 192 mM glycine, 0.1% SDS). Among the five protocols tested for gel storing, success was attained when the gels were stored in plastic bags with 50% glycerol. This is the first report describing the successful solubilization and 2D-electrophoresis of proteins from human lymph node tissue and a 2-D gel storage protocol for easy gel handling before mass spectrometry (MS) analysis.
Keywords: buffer; detergent; protein; tumor protein; cell; chemistry; comparative study; head and neck tumor; human; isoelectric focusing; lymph node; methodology; solubility; squamous cell carcinoma; standard; time; two dimensional gel electrophoresis; Buffers; Carcinoma, Squamous Cell; Cells; Detergents; Electrophoresis, Gel, Two-Dimensional; Head and Neck Neoplasms; Humans; Isoelectric Focusing; Lymph Nodes; Neoplasm Proteins; Proteins; Solubility; Time